Peran Perawat Komunitas dalam Pencegahan Komplikasi Pada Pasien Hipertensi di Puskesmas Sikumana Kota Kupang - Israfil Israfil; Maria Agustina Making (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2019)
Complications of hypertensive patients are expected to continue to increase. Integrated Health Center of Sikumana, Kupang City is one of the major health centers that have a high case of hypertension complications in Kupang City, NTT Province. The objective of this study is to determine the role of community nurses in the prevention of complications in hypertensive patients at the Integrated Health Center of Sikumana, Kupang City. The research method is descriptive with a survey design. The population in research is nurses in the Integrated Health Center of Sikumana, Kupang City comprising 21 people. The sample was taken from the total population with inclusion criteria of PNS (civil servant) and PTT (non-permanent employee) nurses from the government, minimum education of Nursing D-III, and working period ≥ 2 years. The results showed 52.4% of nurses assessed risk factors for complications in hypertensive patients, 81% formulated nursing diagnoses, 76.2% developed intervention plans, 76.2% implemented, 54.5% conducted community empowerment, 85.7% conducted health education, 95.5% conducted referral in prevention complications in hypertensive patients. It can be concluded that the role of community nurses in the prevention of complications in hypertensive patients in Integrated Health Center of Sikumana, Kupang City has largely been conducted well, and it is recommended that nurses at the Integrated Health Center have participated actively in following various training and work on the community nursing process to comply with the latest instructions and regulations.